2017
DOI: 10.1007/s40266-017-0455-9
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Risk of Delirium with Different Opioids: A Systematic Review

Abstract: ObjectiveThere is substantial evidence that the use of opioids increases the risk of adverse outcomes such as delirium, but whether this risk differs between the various opioids remains controversial. In this systematic review, we evaluate and discuss possible differences in the risk of delirium from the use of various types of opioids in older patients.MethodsWe performed a search in MEDLINE by combining search terms on delirium and opioids. A specific search filter for use in geriatric medicine was used. Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 31 publications
3
82
0
1
Order By: Relevance
“…All participants in this study received intrathecal diamorphine. The independent association between additional intraoperative intravenous opioid administration and postoperative delirium is in keeping with broader published evidence associating opioids and delirium in hospitalised patients (44) however studies examining intraoperative intravenous opioids are limited (45). The numbers of participants receiving fentanyl in our study are too small to challenge recent findings suggesting it is a safer opioid however the relatively high numbers receiving alfentanil, and the limited evidence base available assessing delirium risk in elderly elective surgical populations require further study.…”
Section: Discussionsupporting
confidence: 80%
“…All participants in this study received intrathecal diamorphine. The independent association between additional intraoperative intravenous opioid administration and postoperative delirium is in keeping with broader published evidence associating opioids and delirium in hospitalised patients (44) however studies examining intraoperative intravenous opioids are limited (45). The numbers of participants receiving fentanyl in our study are too small to challenge recent findings suggesting it is a safer opioid however the relatively high numbers receiving alfentanil, and the limited evidence base available assessing delirium risk in elderly elective surgical populations require further study.…”
Section: Discussionsupporting
confidence: 80%
“…Approximately one in six patients diagnosed with delirium in this study were taking opioid analgesics before hospital admission. Prior studies have shown that opioids are frequently associated with delirium 27 ; however adding to the complexity in interpreting the association between medicines and delirium, uncontrolled pain is also a risk factor Psycholeptics-opioids 175 (11) 817 (8) 191 (9) Psycholeptics-antidepressants 374 (23) 1356 (13) 352 (17) Psycholeptics-cardiac medications 92 (6) 408 (4) 99 (5) Psycholeptics-antihypertensives 424 (26) 1848 (18) 460 (22) Psycholeptics-systemic corticosteroids 75 (5) 426 (4) 109 (5) Opioids-antidepressants 220 (13) 943 (9) 248 (12) Opioids-cardiac medications 67 (4) 314 (3) 71 (3) Opioids-antihypertensives 282 (17) 1456 (14) 346 (17) Opioids-systemic corticosteroids 73 (4) 435 (4) 85 (4) Antidepressants-cardiac medications 115 (7) 535 (5) 121 (6) Antidepressants-antihypertensives 508 (31) 2257 (22) 589 (28) Antidepressants-systemic corticosteroids 102 (6) 517 (5) 134 (6) Antihypertensives-cardiac medications 238 (15) 1259 (13) 299 (14) Antihypertensives-systemic corticosteroids 132 (8) 916 (9) 200 (10) Cardiac medications-systemic corticosteroids 48 (3) 237 (2) 47 (2) a Results presented for medicines used by greater than 10% of study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Another study performed in a surgical context reported that tramadol and meperidine were associated with an increased risk of delirium but use of morphine, fentanyl, oxycodone, and codeine were not. 31 Two studies implemented in the surgical field simultaneously examined the relationship between pain, opioids, and delirium. 32,33 The first study, performed on patients with hip fractures, suggested that untreated pain and opioid underuse were important contributors to the development of delirium.…”
mentioning
confidence: 99%